Factors Influencing Generation Z's Intention to Purchase Environmentally Friendly Skincare Products - Renza Fahlevi; Valeska Lilya Kevin; Fitriana Aidnilla Sinambela (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study aims to explore how factors such as environmental concern (EC), subjective norms (SN), perceived behavioral control (PBC), and environmental attitude (EA) influence Generation Z, specifically their intention to purchase environmentally friendly skincare products.Method: A quantitative research approach was employed, with a sample of 200 Generation Z consumers who have purchased environmentally friendly skincare products. The respondents were selected using purposive sampling, based on criteria including being born between 1995 and 2010, residing in Batam, and having purchased environmentally friendly skincare products. Data analysis was conducted using SPSS and SmartPLS software.Result: The findings reveal that environmental concern (EC), perceived behavioral control (PBC), and environmental attitude (EA) significantly influence green purchase intention (GPI), while subjective norms (SN) do not have a significant effect. Additionally, SN and PBC influence GPI through EA, whereas EC does not significantly impact GPI via EA.Practical Implications for Economic Growth and Development: The results of this study offer valuable insights for companies in the environmentally friendly skincare sector, helping them tailor effective marketing strategies to Generation Z consumers' preferences. By implementing the right strategies, companies can boost product sales and contribute to broader economic growth.